PENURUNAN ANGKA ASAM PADA MINYAK JELANTAH - Mardina, Primata; Faradina, Erlyta; Setiawati, Netty (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012, 2013)
Acid number expresses free fatty acid content that has effect on quality of oil and fat product. High acid number in resulted from hydrolysis process that occurred during frying. Acid number could be reduced by adsorption. The objective of this research was to reduce acid number from waste cooking oil using adsorption process. The activated carbon from coconut shell was used as adsorbent. A specific amount of adsorbent was added into 150 grams of waste cooking oil, and the process was carried out with certain range of operation time. Stirring speed and temperature of adsorption process were maintained constant at 500 rpm and 27 o C. The result showed free fatty acid adsorption or reduction in acid number efficiencies increase with higher adsorbent doses. Based on the result, the reduction in acid number of waste cooking oil using activated coconut shell carbon followed the Freundlich-type isotherms.
Keywords: acid number, waste cooking oil, isotherm adsorption Freundlich